THE ROLE OF THE MANAGER-INNOVATOR IN THE MANAGEMENT AND PROJECT ACTIVITIES - HAVLOVSKA, Nataliia; RUDNICHENKO, Yevhenii; KRYVDYK, Mykhailo; BALABUST, D.; GARBUZIUK, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the peculiarities of the formation of the innovative worldview of the manager-innovator and highlights the main characteristics of the innovative personality from the position of making managerial decisions in project and managerial activities. The differences between the understanding of the essence and deep meaning of the activity of innovators and innovators have been given. It has been proven that an innovative leader must be endowed with risk-oriented thinking, which involves not only the ability to take risks, but also to analyze the causes of existing deviations in processes, systems, etc., to be able to apply previous experience, to make the most of available opportunities and to avoid unreasonable risks. Innovative managers are able to create new solutions, products, etc. that give consumers new quality. They embody completely new ideas that are unique and lead to disruptive innovations. Therefore, an innovative leader should be understood as a creative manager, a generator of unique ideas, the implementation of which gives the market a new quality. The leader-innovator has inherent leadership qualities that allow him to introduce innovations. Not all managers can be innovative. Only a small part of people can produce innovations and implement them. To implement innovations, only knowledge and skills are not enough, one should have specific behavioral skills and intuitive innovative abilities. That is, innovative leaders have a special way of thinking that prompts them to make non-standard and unique solutions. An innovative vision of business development plays a special role in project activities, since almost any project involves the implementation of new ideas and management approaches. The given model of creative thinking is relevant not only in the implementation of innovative projects, it is mandatory for successful management activities in modern conditions of turbulent changes.
Keywords: manager; innovator; managerial activity; project activity; management